Franjo Radšel (1899–1987), Leader of the Fight against Tuberculosis in Northeast Slovenia from 1936 to 1976 - Zvonka Zupanič Slavec; Ksenija Slavec (Zdravniški Vestnik, 2010)
Franjo Radšel (1899–1987) dedicated his life to the fight against tuberculosis. He started his career at the Golnik Sanatorium, and continued at the Slovenj Gradec Hospital and Maribor Hospital, where he headed the pulmonary ward. He set up antituberculosis clinics in the towns of Črna, Lenart, Šentilj, Oplotnica and Poljčane and he worked at outpatient clinics in Trbovlje, Slovenska Bistrica, and Maribor. In his half century of effort (from 1926 to 1976), he carried out pioneering work in the fight against tuberculosis, contributed to the development of antituberculosis services in northeast Slovenia, and described the development of this service in Maribor.